Mozambique : Public Expenditure Review for the Water Sector - World Bank (Washington, DC, 2013)
Reform is definitely under way in the water sector. Mozambique's goals and macro strategies are laid out in the Poverty Reduction Action Plan (PARPA) which is the main reference for water supply and sanitation policies. A water policy was established in 2007 which sets national targets for water supply and sanitation coverage, specifically, to achieve the millennium development goals. The sector also has a national strategy for the management of water resources. In addition, the different water subsectors have generated a large set of additional plans and strategies. The Medium-Term Fiscal Framework (MTFF) with specific proposals for each institution or agency in the sector, and the Economic and Social Plan for Rural Agriculture. The concurrence of these planning documents at the provincial and local levels requires strong coordination to ensure that the sector uses an integrated approach that balances the interests of the different sub-sectors with that of the overall sector. Yet, currently the sector still lacks a strong coordination mechanism. As a result of these policy changes, the Government's actual expenditure for the sector increased from $27 million in 2002 to $95 million in 2008; this is unlikely to be the total of funding available in the sector, but what could be substantiated from the government accounts. Donors supply most of funding in the form of investment funding. This public expenditure review focuses on the quantity and quality of Mozambique's public funding process to assess how well budget allocations for the water sector actually translate into better water and sanitation service delivery.